The study of GSDMB in pathogenesis of psoriasis vulgaris. - Xiaojuan Ji; Huaqing Chen; Ling Xie; Shiqi Chen; Shan Huang; Qi Tan; Huifang Yang; Tao Yang; Xiaoying Ye; Zhaolin Zeng; Chunlei Wan; Longnian Li (PLoS ONE, 2023)
Background Gasdermin (GSDM) B is a member of the GSDM family, which is a protein that may be involved in the cell pyroptosis process and is associated with inflammatory diseases. Objective To explore the correlation between GSDMB and psoriasis vulgaris. Methods Skin lesions from 33 patients with psoriasis vulgaris and 69 normal controls were collected. ELISA and Western blot were adopted to detect proteins. The HaCaT cell line was transfected with 3 sets of interfering sequence siRNA, and the mRNA and protein levels before and after the transfection were measured by qPCR and Western blot respectively, so as to establish a cell model with low GSDMB gene expression; the MTT method was used to detect cells viability, flow cytometry to detect cell apoptosis. Results The level of GSDMB protein in the skin lesions of patients with psoriasis vulgaris was lower than that in normal skin tissues (P < 0.05). The mRNA and protein expression levels of the target gene in the siRNA-GSDMB-3 group were lower than those in the control group (P < 0.05). The proliferation of HaCaT cells was decreased by MTT method and flow cytometry, and the apoptosis rate was increased (P < 0.05). Conclusion The expression level of GSDMB in psoriasis vulgaris lesion tissue is lower than that of normal skin tissue. The down-regulation of GSDMB expression can inhibit cell proliferation and promote cell apoptosis. GSDMB may play a role in the pathogenesis of psoriasis by affecting the differentiation of keratinocytes and the function of T cells.